Transformation The Indonesian Military in the Revolutionary Era Industry 4.0: Integrative Model and Digital HR Strategy - Totok Imam Santoso; Mia Kusmiati (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Purpose – Purpose study This is For explore How management source Power human (HR) functions as a strategic pillar in develop economy resilient and adaptive defense in the global era . Research This integrate policy national , power competition industry defense , and work The same international through HR- based approach global competence . Design/ methodology / approach – Research This use method review library systematic (Systematic Literature Review/SLR), analyzing more of 50 peer-reviewed articles from journal published Scopus / WoS indexed between 2021–2025 . Research This synthesize framework Work from strategic human resources , economics defense , and global collaboration . Findings – Research This find that HR is not just function administrative , but play role strategic in form strength defense through development source Power people , digital literacy , and work The same cross- country research this also reveals that success synergy industry defense is greatly influenced by the readiness of human resource actors to integrate innovation , diplomacy , and knowledge transnational . Implications practical – For operationalize findings this , policy defense national must invest in centers featured human resource development , design repeat curriculum aligned defense​ with global threats and technologies , as well as build partnership strategic HR with actors​ defense international . Originality / Value – Study This was the first to conceptualize framework Work integrative which places HR as the core of transformation economy defense in a post-pandemic global landscape driven by digitally . Study This offer novelty theoretical with connect economy defense with strategic HR practices , as well as relevance practical for the makers policy and educators defense .